A new species of broad-nosed bat Platyrrhinus Saussure, 1860 (Chiroptera: Phyllostomidae) from the Guianan Shield - Velazco, Paúl M.; Lim, Burton K. (Zootaxa, 2014)
A new species of broad-nosed bat Platyrrhinus Saussure, 1860 (Chiroptera: Phyllostomidae: Stenodermatinae) from the Guianan Shield is described based on molecular and morphological data. Previously confused with P. helleri and P. recifinus, the new taxon is currently known from only Guyana and Suriname and is most closely related to P. recifinus from eastern Brazil and not to the two sympatric species (P. fusciventris and P. incarum) also recently recognized as distinct from P. helleri. Morphometrically the new taxon overlaps with the smaller species of the genus (P. angustirostris, P. brachycephalus, P. fusciventris, P. helleri, P. incarum, and P. matapalensis), but forms a different cluster from the larger P. recifinus. Morphologically the new taxon is distinguished from its congeners by a combination of external and craniodental characteristics. Platyrrhinus now includes 21 species making it the most speciose genus in the Neotropical family Phyllostomidae.